Penanaman Nilai-nilai Akhlakul Karimah pada Peserta Didik melalui Kegiatan Kultum di SD Angkasa 1 Lanud Padang - Idris, Fahmi; Nurjanah, Nurjanah (ALSYS, 2024)
The cultivation of the values of karimah in the pupils is very necessary, given the development of the times and the science of education, and is accompanied by negative effects. Therefore, it is necessary to cultivate the values of achlakul karimah in the students. This research aims to describe the cultivation of the values of the achlakul karimah in the pupils at SD Space 1 Lanud Padang. As for the method of this research, it is a qualitative research method with a case study approach. Data collection techniques use methods of interview, observation, and documentation. Data analysis is accompanied by data reduction, data display, and conclusion drawings. The results of this study showed that (1) the activities of the cult in SD Space 1 Lanud Field consist of three stages, namely the initiation activities, core activities, and closing activities, (2) the cultivation of the values of achlakul karimah in the pupils consists of three phases: the stages of value transformation, the stage of value transaction, and the stage transinternalization of value; (3) there are supportive and inhibitory factors in the establishment of values, supporting factors include the will of students to be better, teachers always give a good example, support from parents, adequate means and facilities, the giving of rewards and values to students, while the impeding factors included the factor of students who do not want to change, family factors that do not support, and environmental factors that don't support.